OPTIMIZATION OF CALCULATION SCHEMES (Collection of scientific works «Modern structures of metal and wood», 2021)
Any  calculation  is preceded by  the  stage  of  creating  a  design  diagram  of  a  real structure, which would most accurately correspond to real operating conditions.  The more optimally the  design  scheme  is  drawn  up,  the  less  laborious  the  stages  of  calculation  and  design  of  the corresponding  structure  will  be.    There  are  practically  no  results  of  using  this  approach  when calculating building structures.  This article attempts to show the possibility and expediency of using the  "Search  for  solutions"  (add-on  for  Microsoft  Excel)  at  the  stage  of  choosing  the  optimal parameters of the design design schemeAny calculation is preceded by the stage of creating a design diagram of a real structure, which would most closely correspond to real operating conditions.  The more optimally the design scheme is drawn up, the less laborious the stages of calculation and design of the corresponding structure will be.  If the efficiency criterion is a linear function, and the variables in the constraint system are also linear, then such a problem is a linear programming problem.  Of the listed  methods  of  mathematical  programming,  the  most  common  and  developed  is  linear programming. To illustrate the idea of the proposed approach, a simple statically definable truss on two supports was deliberately chosen.  This is done so that the idea of the proposed approach is not lost due to the complexity and cumbersomeness of the calculations.  This article shows the possibility and feasibility of using the "Search for solutions" at the stage of choosing the optimal parameters of the design design scheme.  After the design scheme has been defined, more powerful conventional means of calculating building structures can be involved for its complete calculation.